High-Skilled Migration from Myanmar: Responses to Signals of Political and Economic Stabilization - Yashodhan Ghorpade; Muhammad Saad Imtiaz; Theingie Han (Institute of Labor Economics (IZA), 2025)
In recent years Myanmar has witnessed considerable economic and political instability, leading many young people, particularly the higher-skilled, to consider migrating abroad for improved prospects. We employ an innovative method to quantify migration intentions among high-skilled youth by analyzing the take-up of migration at different wage premia. A randomized survey experiment then evaluates how hypothetical political and economic stabilization scenarios impact these intentions. We find that 35 percent of the respondents would be willing to take a similar job abroad for pay equal to their current income. Randomization within the survey indicates that political stabilization would potentially reduce high-skilled workers' desire to migrate by about 15 percent, especially among men, those living in high conflict areas, and persons with lower absolute income, but higher perceived relative income. In contrast, prospects of economic stabilization do not have a significant effect on migration intentions. Economic stabilization, in the absence of political stability and a reduction in conflict, is unlikely to reduce talent outflows among the young.
Keywords: J61; O15; D74; F2; 330; migration; emigration; Myanmar; brain drain; high-skilled migration; conflict